1977
DOI: 10.1111/j.1464-410x.1977.tb04158.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Ureteric Nipple Alone for Reflux prevention

Abstract: In the re-implantation of a ureter into the bladder, vesico-ureteric reflux can be prevented by a ureteric nipple alone, provided the nipple is at least 1.5 cm long. This eliminates the need for an oblique ureteric entry or a submucosal tunnel. Longer nipples may be used although they may lead to difficulties with catheterisation. Reduction in the length of the nipple frequently occurs later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The bladder is opened by a midline incision, the ureteric orifice circumcised and the intravesical ureter dissected free from the bladder. A nipple, not less than 2cm but no longer than 2.5 cm, is constructed using the technique similar to that of Urquhart-Hay et al (1977) with a few minor modifications; the nipple is constructed outside the bladder and to prevent unrolling, the everted edge is sutured to the outer ureteric wall before it is delivered into the bladder.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bladder is opened by a midline incision, the ureteric orifice circumcised and the intravesical ureter dissected free from the bladder. A nipple, not less than 2cm but no longer than 2.5 cm, is constructed using the technique similar to that of Urquhart-Hay et al (1977) with a few minor modifications; the nipple is constructed outside the bladder and to prevent unrolling, the everted edge is sutured to the outer ureteric wall before it is delivered into the bladder.…”
Section: Resultsmentioning
confidence: 99%
“…Fam (1964) Table Salient Features of the 10 Patients to-side ureterovesical anastomosis which has been widely employed in bilharzial surgery (Ghoneim et ai., 1971;Mee and Youssef, 1982). Urquhart-Hay et al (1977) have recently reported the anti-reflux potential of vesicoureteric reimplantation by constructing a nipple from a dilated ureter without submucosal tunnelling. This is a simple technique but there is no previous report of its use in the management of dilated ureters, bilharzial or otherwise.…”
mentioning
confidence: 99%
“…The ureter was straightened; the distal redundancy will be excised. [13]. The authors stated that to prevent the reflux the nipple must be at least 15 mm in length.…”
Section: Figurementioning
confidence: 99%
“…and evaluate the antireflux effect of this technique. We hypothesized that a nipple valve of 20 mm length would result in less reflux than the 10-15 mm length nipple, as has been reported in the literature [12,13].…”
mentioning
confidence: 91%
See 1 more Smart Citation